La casa: una ricerca su un luogo molto derubato e poco studiato (Società e diritti, 2021)
AbstractThis article presents an overview of the principal results of our research on burglaries, a little-discussed and studied topic. Our research has gone on for twenty years (with interruptions), and has accumulated an impressive amount of data, in a comparative perspective and with extensive references to the classics of sociology, criminology, and literature.The phenomenon appears very relevant (since it affects millions of people), politically significant (since it concerns the trust in the institutions of these millions of citizens), risky (since it highlights the institutional responsibilities, denounced by citizens as unbearable). Unfortunately and unintentionally, the principal results of our research are not politically correct.A research on burglaries has gradually become a research on the relationship of the citizens with the State, understood as the large "home" of the Italians and generally perceived as a house that would need a better defense from thieves as well as a profound renovation.sociology, trust, politics, burglary